Maternal serum Vitamin B12 and offspring attention-deficit/hyperactivity disorder (ADHD) - Sourander Andre; Silwal Sanju; Upadhyaya Subina; Surcel Heljä-Marja; Hinkka-Yli-Salomäki Susanna; McKeague Ian W.; Cheslack-Postava Keely; Brown Alan S. (Springer, 2022)
Maternal Vitamin B12 deficiency during pregnancy is associated with offspring neuropsychiatric disorders. Few previous studies examining this association with attention-deficit/hyperactivity disorder (ADHD) report inconsistent findings. The study examines the association between maternal serum Vitamin B12 levels and offsprings’ risk of ADHD. This study is based on the Finnish Prenatal Study of ADHD with a nested case–control design. All the singleton children born in Finland between January 1998 and December 1999 and diagnosed with ADHD were included in the study. A total of 1026 cases were matched with an equal number of controls on sex, date of birth and place of birth. Maternal Vitamin B12 levels were assessed using a chemiluminescence microparticle immunoassay and archived from maternal serum banks, collected during the first and early second trimester of pregnancy. Lower maternal Vitamin B12 levels when analyzed as a continuous variable was not associated with offspring ADHD (aOR 0.97, 95% CI 0.79–1.18, p = 0.75). No significant associations were seen in the lowest quintile of Vitamin B12 levels (aOR 0.96, 95% CI 0.73–1.27, p = 0.80). This is the first study examining maternal sera Vitamin B12 levels during early pregnancy and offspring ADHD. The result suggests that Vitamin B12 deficiency during early pregnancy has specificity for some disorders but not with offspring ADHD.